2005
DOI: 10.1089/end.2005.19.827
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Ureteropelvic Junction Obstruction by Division of Anterior Crossing Vein and Cephalad Relocation of Anterior Crossing Artery

Abstract: Select cases of UPJ obstruction associated with anterior crossing vessels seem to be amenable to laparoscopic management by division of the crossing vein and cephalad relocation of the crossing artery. Laparoscopy as a minimally invasive approach may offer a better opportunity to evaluate the role of anterior crossing vessels in UPJ obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The need for narcotic or nonnarcotic analgesic after in laparoscopic surgery has been found to be lower than for the open pyeloplasty technique (13). In our study, the median need for narcotic analgesics was 21.5±4.8 mg (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), which is compatible with what appears in the literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The need for narcotic or nonnarcotic analgesic after in laparoscopic surgery has been found to be lower than for the open pyeloplasty technique (13). In our study, the median need for narcotic analgesics was 21.5±4.8 mg (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), which is compatible with what appears in the literature.…”
Section: Discussionsupporting
confidence: 88%
“…We observed aberrant vessels in 19 patients (57.6%) in our study. It has been advised that even though aberrant vessels are the most common cause of UP stenosis, other causes should be kept in mind (16 (18). In our study, only one case recurred 6 months after surgery, but 32 patients showed improvement in ultrasonic and renographic findings.…”
Section: Discussionmentioning
confidence: 54%
“…Previously, Simforoosh et al reported outcomes of division of crossing vein and cephalad relocation of crossing artery in 10 adult patients with UPJO [5]. In the present series, we have shown the value of this technique in pediatrics: 22.2% (14/63) of our patients had lower pole crossing vessels and drainage of the renal pelvis was significantly improved in more than half of them (9/14, 64.3%) after laparoscopic cephalad relocation of crossing artery.…”
Section: Discussionmentioning
confidence: 99%
“…After inspecting ureteral peristalsis across the UPJ and adequate drainage of the renal pelvis, the crossing vein was divided and cauterized in bipolar mode, while the crossing artery was preserved and relocated cephalad and affixed with two or three absorbable sutures (Fig. 1A,B) [5]. With this technique, there is no requirement for double J stent insertion, so repeat anesthesia for ureteral stent removal is avoided.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation